Dosimetry study of 3D-printed noncoplanar template-assisted CT-guided 125I seed implantation for the treatment of recurrent and metastatic tumors in the head and neck - Lingyun Qiu; Rong Wu; Yinan Chen; Haixin Xiang; Wenming Zhan; Yinghao Zhang; Qiang Li; Huaxin Liu; Jieni Ding; Yucheng Li; Aihong Bi; Limin Luo; et al. (PLoS ONE, 2025)
Objective Recurrent and metastatic tumors of the head and neck pose significant treatment challenges due to their proximity to critical structures and prior radiation exposure. This study aimed to evaluate the consistency between preoperative and postoperative dosimetric parameters in CT-guided 3 D-printed noncoplanar template (3DPNCT)-assisted radioactive iodine-125 seed implantation (RISI). Methods Twenty-six patients with recurrent or metastatic head and neck cancer were retrospectively analyzed. Gross tumor volume (GTV) coverage and dosimetric parameters such as D90 (dose covering 90% of the GTV), conformity index (CI), and homogeneity index (HI) were compared before and after implantation. The Shapiro-Wilk test was used to assess data normality. Results There were no significant differences between pre- and postoperative D90, V100, V150, or CI values (P > 0.05). Bland–Altman analysis showed high agreement for key metrics. Conclusions 3DPNCT-assisted RISI demonstrated accurate dose delivery and high reproducibility. This approach may enhance local control while minimizing radiation to organs at risk in complex head and neck anatomies. These results suggest that this technique has promising clinical applicability in complex head and neck cases; however, further validation through larger prospective studies is warranted to confirm long-term efficacy and safety.